2007
DOI: 10.1038/modpathol.3800825
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of LINE-1 and Alu in well-differentiated neuroendocrine tumors (pancreatic endocrine tumors and carcinoid tumors)

Abstract: Neuroendocrine tumors including carcinoid tumors and pancreatic endocrine tumors are uncommon, and the genetic alterations in these indolent tumors are not well characterized. We studied global hypomethylation by analyzing long interspersed nucleotide elements (LINE)-1 and Alu methylation using pyrosequencing in 35 neuroendocrine tumors and corresponding normal tissue. The tumor samples were less methylated than normal tissue at LINE-1 (P ¼ 0.04) and Alu (P ¼ 0.001). The mean relative tumor hypomethylation (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 37 publications
(54 reference statements)
11
119
0
Order By: Relevance
“…Transcriptional inactivation of tumor suppressor genes by promoter CpG island methylation is an important mechanism in human carcinogenesis. 2,[34][35][36][37][38] To measure the degree of DNA methylation, we used quantitative PCR assays (MethyLight), 20 which is essential to reproducibly differentiate low-level methylation from high-level methylation. 21,24 Our resource of a large number of samples of colorectal cancer (relatively unbiased samples compared to retrospective or single-hospital-based samples), derived from two large prospective cohorts, has enabled us to precisely estimate the frequency of low-level CpG island methylation in colorectal cancers at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional inactivation of tumor suppressor genes by promoter CpG island methylation is an important mechanism in human carcinogenesis. 2,[34][35][36][37][38] To measure the degree of DNA methylation, we used quantitative PCR assays (MethyLight), 20 which is essential to reproducibly differentiate low-level methylation from high-level methylation. 21,24 Our resource of a large number of samples of colorectal cancer (relatively unbiased samples compared to retrospective or single-hospital-based samples), derived from two large prospective cohorts, has enabled us to precisely estimate the frequency of low-level CpG island methylation in colorectal cancers at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…However, epigenetic changes such as genome-wide hypomethylation of LINE-1 and Alu-repetitive sequences and promoter hypermethylation of specific genes, i.e. RASSF1A, CTNNB1, LAMB3, CDKN2A, CDH1, LAMC2 and THBS1, have been reported in a subset of tumours (Chan et al 2003, Liu et al 2005, Zhang et al 2006, Choi et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Huan Cheng, Meng Lu, Li-Jun Mao, Jun-Qi Wang, Wang Li, Ru-Min Wen, Jia-Cun Chen* with changes in this epigenetic phenomenon, including two distinct and seemingly opposing trends: global decrease in cytosine methylation (hypomethylation or unmethylation) and methylation of cytocine in CpG islands (hypermethylation) (Choi et al, 2007). One study done in Espana demonstrated that neoplasia is correlated with overall genomic hypomethylation (Gonzalo et al, 2008), failure to repress genes appropriately by abnormal demethylation of tissue-restricted genes or by hypomethylation of proto-oncogenes could result in the loss of tissue specificity and could promote cancer formation.…”
Section: Relationships Among Mthfr A1298c Gene Polymorphisms and Methmentioning
confidence: 99%